The CDAA Framework for development of sustainable large-scale smallholder irrigation schemes in Swaziland - Dlamini, Nkululeko Simeon; Kamal, Md. Rowshon; Makhanya, M.; Sithole, S. (Elsevier (ScienceDirect), 2014)
Poverty affects nearly a billion of the world population and many of these people are living in rural communities. Smallholder irrigation development plays a pivotal role in reducing rural poverty. Many smallholder schemes have failed in the past due to poor planning and community disputes. This paper presents a promising framework, the CDAA, for developing sustainable smallholder irrigation schemes which is currently applied in the LUSIP project in Swaziland. The strength of the framework is that; 1) it makes the primary beneficiary (community) the main driver of the development, and 2) it significantly changes the economic state of the community.